Cabozantinib in patients with advanced Ewing sarcoma or osteosarcoma (CABONE): a multicentre, single-arm, phase 2 trial. Issue 3 (March 2020) - Italiano, Antoine; Mir, Olivier; Mathoulin-Pelissier, Simone; Penel, Nicolas; Piperno-Neumann, Sophie; Bompas, Emmanuelle; Chevreau, Christine; Duffaud, Florence; Entz-Werlé, Natacha; Saada, Esma; Ray-Coquard, Isabelle; Lervat, Cyril; et al.
Summary: Background: Patients with Ewing sarcoma or osteosarcoma have a median overall survival of less than 12 months after diagnosis, and a standard treatment strategy has not yet been established. Pharmacological inhibition of MET signalling and aberrant angiogenesis has shown promising results in several preclinical models of Ewing sarcoma and osteosarcoma. We aimed to investigate the activity of cabozantinib, an inhibitor of MET and VEGFR2, in patients with advanced Ewing sarcoma and osteosarcoma. Methods: We did a multicentre, single-arm, two-stage, phase 2 trial in patients with advanced Ewing sarcoma or osteosarcoma recruited from ten centres in the French Sarcoma Group. Key eligibility criteria were aged 12 years or older, Eastern Cooperative Oncology Group performance status of 0–1, and documented disease progression (according to Response Evaluation Criteria in Solid Tumors version 1.1) before study entry. The number of previous lines of treatment was not limited. Patients received cabozantinib (adults 60 mg, children [<16 years] 40 mg/m 2 ) orally once daily in 28-day cycles until disease progression, unacceptable toxicity, the investigator's decision to discontinue, or participant withdrawal. The primary endpoint for Ewing sarcoma was best objective response within 6 months of treatment onset; for osteosarcoma, a dual primary endpoint of 6-month objective response and 6-month non-progression was assessed. All enrolled patients who received at least one dose of cabozantinib were included in the safety analysis, and all participants who received at least one complete or two incomplete treatment cycles were included in the efficacy population. This study was registered with ClinicalTrials.gov, number NCT02243605 . Findings: Between April 16, 2015, and July 12, 2018, 90 patients (45 with Ewing sarcoma 45 with osteosarcoma) were recruited to the study. Median follow-up was 31·3 months (95% CI 12·4–35·4) for patients with Ewing sarcoma and 31·1 months (24·4–31·7) for patients with osteosarcoma. 39 (87%) patients with Ewing sarcoma and 42 (93%) patients with osteosarcoma were assessable for efficacy after histological and radiological review. In patients with Ewing sarcoma, ten (26%; 95% CI 13–42) of 39 patients had an objective response (all partial responses) by 6 months; in patients with osteosarcoma, five (12%; 4–26) of 42 patients had an objective response (all partial responses) and 14 (33%; 20–50) had 6-month non-progression. The most common grade 3 or 4 adverse events were hypophosphataemia (five [11%] for Ewing sarcoma, three [7%] for osteosarcoma), aspartate aminotransferase increase (two [4%] for Ewing sarcoma, three [7%] for osteosarcoma), palmar-plantar syndrome (three [7%] for Ewing sarcoma, two [4%] for osteosarcoma), pneumothorax (one [2%] for Ewing sarcoma, four [9%] for osteosarcoma), and neutropenia (two [4%] for Ewing sarcoma, four [9%] for osteosarcoma). At least one serious adverse event was reported in 61 (68%) of 90 patients. No patients died from drug-related toxic effects. Interpretation: Cabozantinib has antitumor activity in patients with advanced Ewing sarcoma and osteosarcoma and was generally well tolerated. Cabozantinib could represent a new therapeutic option in this setting, and deserves further investigation. Funding: Institut Bergonié; French National Cancer Institute; Association pour la Recherche contre le Cancer.